A holistic review of nanomaterials in strain-hardening cementitious composites: Insights into micro- and macromechanical, deformation, smart, and durability properties - Isyaka Abdulkadir; Leong Sing Wong; Lee Woen Ean; G. Murali; Bashar S. Mohammed (Results in Engineering)
Strain-hardening cementitious composites (SHCC) are rapidly gaining popularity as building materials because of their remarkable ductility, increased tensile strain capacity, and controlled saturated microcrack propagation with tight crack width. Careful tailoring of materials and fiber-matrix interaction are credited to these exceptional properties. However, the primary challenges to the performance and widespread application of SHCC include the difficulty in achieving an optimum fiber-matrix bonding due to variations in surface properties at the interface, increased porosity because of the incorporation of polymeric fibers, and low modulus of elasticity and high shrinkage due to the absence of coarse aggregates and high cementitious material content. Extensive research has revealed that incorporating nanomaterials (NMs) into SHCC, either directly or as fiber pretreatment, can significantly enhance the matrix properties and the fiber-matrix interfacial transition zone. These enhancements address several key challenges, resulting in improved overall composite performance. Different types of NMs, such as nano silica (NS), and carbon-based nanomaterials—including carbon nanotubes/nanofibers (CNTs/NFs), graphene oxide (GO), and carbon black (CB)—influence SHCC behavior through multiple mechanisms. These mechanisms include refining the pore structure, improving the interfacial transition zone (ITZ) between the fibers, cementitious matrix, and aggregates, and providing additional nucleation sites for cement hydration products. These contributions lead to enhanced mechanical properties, durability, and energy absorption capacity. Furthermore, NMs play a crucial role in crack bridging and crack tip shielding, both of which are essential for achieving the strain-hardening behavior characteristic of SHCC. This review aims to explore the roles and effectiveness of various NMs in enhancing the critical properties of SHCC, including micromechanical, macromechanical, smart, and durability characteristics. By examining current trends in nanotechnology research applied to SHCC, the review seeks to inform future strategies for the efficient selection and application of nanomaterials in SHCC. The review's outcome is significant as it provides valuable insights into the influence of nanomaterials on improving the properties of SHCC. These improvements include reducing porosity, expediting cement hydration, inducing denser microstructure, enhancing fiber bridging capacity, stimulating self-healing and self-sensing capabilities, and boosting durability.